Teaching English amidst Coronavirus Pandemic in Bangladesh: Technological Adaptations and Pedagogical Modifications - Hossain, Md. Mozaffor; Rahman, Md. Atiqur (ELTALL: English Language Teaching, Applied Linguistic and Literature, 2023)
This research intended to explore what novel adaptations to the existing technological devices and applications, and what changes to the already-practiced pedagogy the English language teachers of Bangladesh made and implemented to continue teaching English amidst the COVID-19 pandemic. The study utilized the qualitative methodology applying an open-ended questionnaire on 12 English Language Teaching (ELT) teachers from across the country, who taught English language to various levels of students through online mode during the impasse. The findings of the research demonstrated that ELT teachers effectuated dramatic changes and improvisations to the existing technological devices, programs and applications to respond to the new mode of teaching, and exert the best of it. Simultaneously, the results presented that most of the ELT teachers had to inculcate dramatic modifications to the habituated pedagogical practices, a major portion of which was psychological shift and support.